Influences of institutional environment toward the development of supply chain management - Yaibuathet K. (2014)
The development of supply chain operational performance in global context is often limited by some of the institutional constrains. In order to enhance the ability of supply chain operational performance, it is essential for the focal company to understand the institutional environments of the supply chain members. The proper institutional arrangement should be, furthermore, positioned to induce cooperation and motivate all chain members to participate activities that produce reciprocal benefits. The research on supply chain operational performance was carried out in Japan, Thailand and China. The findings indicated that the institutional environment would play important roles in the current performance level and could be one of the main obstacles in improving the supply chain operational performance. In addition, the companies with similar institutional environments were observed to have common way of thinking with respect to supply chain management perception. © 2008 Elsevier B.V. All rights reserved.